Influence of activated carbon surface oxygen functionalities on SO2 physisorption – Simulation and experiment - Furmaniak, S.; Terzyk, A.; Gauden, P.; Kowalczyk, Piotr; Szymanski, G. (Elsevier BV, 2013)
The influence of the gradual oxidation of carbons on SO2 physisorption was studied, by comparison of experimental and simulated SO2 adsorption isotherms. The results confirmed a significant impact of surface groups on the SO2 adsorption. The simulations also revealed a similar, to that observed experimentally, effect of the increase in the percentage of the smallest micropores on adsorption isotherms. The isotherms were analysed using the CMMS model. The conclusion is that this model seems to be a good and sensitive tool for studying SO2 physisorption mechanism since a very good qualitative agreement between the experimental and simulated data was observed.